ANALYSIS OF THE CLINICAL CASE OF SEVERE STROKE IN A PATIENT WITH ADVERSE PROGNOSTIC FACTOR - Марина Анатольевна Пеганова; Елена Алексеевна Полукарова; Сергей Николаевич Филимонов; Светлана Станиславовна Зиборова; Александра Константиновна Волкова; Василий Николаевич Узун (Медицина в Кузбассе)
Objective – demonstration of a clinical case of management patient with severe stroke and severe comorbid pathology.